The sintering and creep and cracking of thermal barrier coatings under thermal cycling. (March 2022) - Cen, L.; Qin, W.Y.; Yu, Q.M.
Highlights: A constitutive model is provided for the sintering and creep of ceramic top-coat. A new three-dimensional finite element model is built for thermal barrier system. The delamination of TGO/bond-coat interface accelerates the top-coat spallation. A static top-coat crack cannot affect the delamination of TGO/bond-coat interface. Abstract: During service, thermal barrier coating will generally go through a series of complicated nonlinear phenomena. In this work, a constitutive framework is provided for the sintering and creep of ceramic top-coat under thermal cycling. The influence of the top-coat sintering and creep was investigated using a three-dimensional thermal barrier system model. It is found that the top-coat sintering gives rise to an obvious reduction in the low-temperature out-of-plane stress within the top-coat but hardly has an effect on the high-temperature out-of-plane stress. The bond-coat/TGO interface is subjected to significant normal stresses upon cooling to ambient temperature, which have greater magnitudes because of the top-coat sintering. Nonetheless, the top-coat creep has very limited effects on the out-of-plane stress within the top-coat and the normal stress across the bond-coat/TGO interface. The cohesive damage model was used to evaluate the delamination of bond-coat/TGO interface under thermal cycling. It is found that the interface delamination could promote the out-of-plane tension of the top-coat and then accelerate the cracking of the top-coat. A static crack is preset in the top-coat to analyze the influence of top-coat crack on the interface delamination. It is found that the top-coat crack hardly affects the normal stresses across the bond-coat/TGO interface and therefore is less likely to facilitate the interface delamination.